Socialism and private enterprise in equatorial Asia : - Freeman, Roger A. (Hoover Institution on War, Revolution, and Peace, Stanford University, 1968)
Contents: Postwar economic growth in equatorial Asia, Malaysia's free enterprise economy, Indonesia's socialist economy.